Solid electrolyte membrane and preparation method and application thereof
By using a double -layer solid electrolyte film in lithium metal batteries, the problem of severe growth of solid electrolyte interface impedance in lithium metal batteries in lithium metal batteries has increased the high energy density and safety performance of the battery.
Patent Information
- Application Number
- CN202411742575.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-01-28
AI Technical Summary
The solid electrolyte interface impedance in lithium metal batteries is large and the lithium dendrites are severely grown, resulting in safety hazards and insufficient energy density.
The solid electrolyte film of the double -layer structure is composed of the first membrane layer and the first polymer. Thickness, optimizing the mechanical performance and electrochemical properties of the membrane.
Increase the cell migration rate of battery, reduce the growth of lithium branches, and enhance the safety performance and high -voltage stability of the battery.
Smart Images

Figure FT_1 
Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of solid electrolyte membranes, and in particular to a solid electrolyte membrane and a preparation method and application thereof. Background Art
[0002] With the rapid development of the portable electronic devices, electric vehicles and energy storage equipment markets, people have put forward higher and higher demands on the comprehensive performance of lithium-ion batteries. Lithium metal batteries have attracted more and more attention due to their high energy density. However, lithium metal batteries face severe problems of lithium dendrite growth, and their potential short circuit risk and flammable liquid electrolytes pose great safety hazards. As research has found, introducing solid electrolytes to replace flammable liquid electrolytes in lithium metal batteries is an effective way to solve safety problems and achieve high energy density. However, common solid electrolytes are relatively brittle, and there are traditional solid-solid contact problems between the positive and negative electrodes, which leads to excessive interface impedance and cannot completely solve the problem of lithium dendrite growth. Summary of the invention
[0003] The present invention provides a solid electrolyte membrane and a preparation method and application thereof, so as to solve the technical problems of large solid electrolyte interface impedance and lithium dendrite growth in lithium metal batteries in the prior art.
[0004] To achieve the above object, the technical solution provided by the present invention is as follows: In a first aspect of the present invention, a solid electrolyte membrane is provided, comprising a first membrane layer and a second membrane layer, wherein the first membrane layer comprises the following components: a quaternary ammonium salt and a first polymer; and the second membrane layer comprises the following components: a lithium salt, a second polymer and an ion conductive ceramic.
[0005] Furthermore, in the first film layer, the mass ratio of the quaternary ammonium salt to the first polymer is 1:8-12.
[0006] Furthermore, in the second film layer, the mass ratio of the lithium salt, the second polymer and the ion conductive ceramic is 6:1-3:1-3.
[0007] Furthermore, the thickness of the first film layer is 5-10 μm, and the thickness of the second film layer is 5-10 μm.
[0008] Furthermore, the quaternary ammonium salt is selected from one or more of octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate, hexadecyl trimethyl ammonium bromide, stearamidopropyl hydroxyethyl quaternary ammonium nitrate, and stearyl trimethyl quaternary ammonium hydrochloride; and the first polymer is selected from one or more of polyethylene oxide, polyacrylonitrile, polymethyl methacrylate, polyethylene glycol methyl ether acrylate, polyethylene glycol diacrylate, and poly N-methylpropionamide.
[0009] Furthermore, the lithium salt is selected from one or more of lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorooxalatoborate, lithium perchlorate, lithium bis(oxalatoborate), lithium tetrafluorooxalatophosphate, and lithium difluorobis(oxalatophosphate); the second polymer is selected from one or more of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, vinylidene fluoride-trifluoroethylene, polyacrylonitrile, polymethyl methacrylate, polyethylene glycol diacrylate, and poly N-methylpropionamide; the ion conductive ceramic is selected from one or more of lithium aluminum titanium phosphate, lithium lanthanum zirconium tantalum oxide, lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide, and lithium phosphorus oxygen nitrogen.
[0010] The second aspect of the present invention provides a method for preparing the above-mentioned solid electrolyte membrane, comprising the following steps: adding the quaternary ammonium salt to a mixed solution of the first polymer and a first solvent, stirring to obtain a first mixed solution, coating it on a glass plate, and drying to form the first film layer; adding the lithium salt to a mixed solution of the second polymer and a second solvent, then adding the powder of the ion conductive ceramic, stirring to obtain a second mixed solution, coating it on the first film layer to form the second film layer, and drying to obtain the solid electrolyte membrane.
[0011] Furthermore, the first solvent is selected from one or more of acetone, anhydrous acetonitrile, N,N-dimethylformamide, and dimethyl sulfoxide; the second solvent is selected from one or more of acetone, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.
[0012] Furthermore, in the first mixed solution, the weight percentage of the quaternary ammonium salt is 0.5% to 1.0%, and the weight percentage of the first polymer is 10% to 15%.
[0013] Furthermore, in the second mixed solution, the weight percentage of the lithium salt is 2% to 10%, the weight percentage of the second polymer is 10% to 15%, and the weight percentage of the ion conductive ceramic is 5% to 10%.
[0014] The third aspect of the present invention provides the use of the above-mentioned solid electrolyte membrane or the solid electrolyte membrane prepared by the above-mentioned preparation method in a lithium metal battery.
[0015] Furthermore, the solid-state lithium metal battery includes a positive electrode plate, a metal lithium negative electrode plate, an electrolyte and the solid electrolyte membrane, the first membrane layer is in contact with the metal lithium negative electrode plate, and the second membrane layer is in contact with the positive electrode plate.
[0016] The solid electrolyte membrane provided by the present invention is provided with two membrane layers, the components of the first membrane layer include quaternary ammonium salt and the first polymer, and the components of the second membrane layer include lithium salt, ion conductive ceramic and the second polymer. The quaternary ammonium salt in the first membrane layer can improve the wettability of the electrolyte membrane, improve the affinity of the electrolyte membrane to the electrolyte, increase the liquid absorption rate of the electrolyte membrane, thereby improving the ion mobility of the battery; and the first membrane layer can form a special lithium affinity matrix with the anions in the electrolyte in the electrolyte, providing adsorption sites for a variety of anions, so that lithium ions can be distributed and deposited more evenly in the special lithium affinity matrix structure, reducing lithium dendrites. The second membrane layer adopts a composite of the second polymer and the ion conductive ceramic, which ensures the ionic conductivity of the electrolyte membrane, and at the same time broadens the electrochemical window, which can improve the stability of the battery under high pressure. The double membrane layer structure of the above-mentioned solid electrolyte membrane enhances the mechanical properties of the electrolyte membrane and improves the safety performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0018] Figure 1 The LSV test results of the solid-state lithium metal battery in the embodiment of the present invention are shown. DETAILED DESCRIPTION
[0019] In order to enable those skilled in the art to better understand the technical solutions in this application, the technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0020] It should be noted that when an element is referred to as being "fixed on" or "set on" another element, it can be directly on the other element or indirectly set on the other element; when an element is referred to as being "connected to" another element, it can be directly connected to the other element or indirectly connected to the other element.
[0021] It should be understood that the terms "length", "width", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc., indicating the orientation or position relationship, are based on the orientation or position relationship shown in the drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.
[0022] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, "multiple" and "several" mean two or more, unless otherwise clearly and specifically defined.
[0023] It should be noted that the structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification for people familiar with this technology to understand and read, and are not used to limit the conditions under which this application can be implemented. Therefore, they have no substantive technical significance. Any structural modification, change in proportional relationship or adjustment of size should still fall within the scope of the technical content disclosed in this application without affecting the effects and purposes that can be achieved by this application.
[0024] In a first aspect of an embodiment of the present application, a solid electrolyte membrane is provided, comprising a first membrane layer and a second membrane layer, wherein the first membrane layer comprises the following components: a quaternary ammonium salt and a first polymer; and the second membrane layer comprises the following components: a lithium salt, a second polymer and an ion conductive ceramic.
[0025] In the embodiment of the present application, the first polymer is preferably a polymer corresponding to the quaternary ammonium salt film, and the second polymer is preferably a polymer corresponding to the ion conductive ceramic film.
[0026] The quaternary ammonium salt in the first film layer can improve the wettability of the electrolyte membrane, improve the affinity of the electrolyte membrane to the electrolyte, and increase the liquid absorption rate of the electrolyte membrane, thereby improving the ion mobility of the battery; and the first film layer in the electrolyte can form a special lithium affinity matrix with the anions in the electrolyte, providing adsorption sites for a variety of anions, so that lithium ions can be distributed and deposited more evenly in the special lithium affinity matrix structure, reducing lithium dendrites.
[0027] The second membrane layer uses a composite of a second polymer and ion-conductive ceramic, which ensures the ionic conductivity of the electrolyte membrane and broadens the electrochemical window, thereby improving the stability of the battery under high voltage.
[0028] The solid electrolyte membrane of the embodiment of the present application is provided with two membrane layers, the components of the first membrane layer include quaternary ammonium salt and the first polymer, and the components of the second membrane layer include lithium salt, ion conductive ceramic and the second polymer. The above double membrane layer structure enhances the mechanical properties of the electrolyte membrane and improves the safety performance of the battery.
[0029] Furthermore, in the first film layer, the mass ratio of the quaternary ammonium salt to the first polymer is 1:8 to 12. In the second film layer, the mass ratio of the lithium salt, the second polymer and the ion conductive ceramic is 6:1 to 3:1 to 3.
[0030] In the first film layer of the embodiment of the present application, under the premise of ensuring the mechanical strength of the first film layer, the mass ratio of the quaternary ammonium salt to the first polymer can achieve the optimal ionic conductivity and lithium ion migration number within the above range.
[0031] In the second film layer of the embodiment of the present application, the mass proportion of lithium salt determines the electrochemical window of the electrolyte membrane. The higher the proportion of lithium salt, the wider the electrochemical window. However, when the mass fraction of lithium salt is too high, the mechanical strength of the solid electrolyte membrane will be significantly reduced; at the same time, it is found through experiments that as the concentration of lithium salt increases, the electrochemical window widens to a certain upper limit. The mass proportion of the second polymer determines the mechanical strength and flexibility of the film. When it is in the above range, a complete, flexible and mechanically strong film can be formed. The mass proportion of ion-conductive ceramics determines the ionic conductivity of the second film layer. The higher the proportion of ion-conductive ceramics, the higher the ionic conductivity. However, when its proportion is too high, it may be easy to agglomerate, destroy the lithium ion transmission path, and reduce the ionic conductivity. Therefore, setting it in the above-mentioned proportion range can make the electrochemical window, ionic conductivity and mechanical strength of the second film layer reach the optimal state.
[0032] In some embodiments, the thickness of the first film layer is 5-10 μm, and the thickness of the second film layer is 5-10 μm. The thickness of the first film layer and the second film layer can increase the transmission speed of lithium ions and enhance the kinetic performance while ensuring the mechanical strength of the solid electrolyte membrane.
[0033] In some embodiments, the quaternary ammonium salt is selected from one or more of octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate, hexadecyl trimethyl ammonium bromide, stearamidopropyl hydroxyethyl quaternary ammonium nitrate, and stearyl trimethyl quaternary ammonium hydrochloride.
[0034] In the embodiments of the present application, the above-mentioned quaternary ammonium salts all contain a quaternary ammonium cation, that is, four organic groups are connected to a nitrogen atom to form a positively charged polyatomic ion. The uneven pore distribution of existing base films such as PP and PE will lead to disordered diffusion of lithium ions and form an uneven deposition layer, which will further lead to continuous consumption of lithium salts and ultimately cause battery failure. The alkyl tail in the above-mentioned quaternary ammonium salt is anchored in the polymer, and its positively charged quaternary ammonium cation interacts with the electrolyte to attract PF6 - Anions can form a lithium-philic integrated matrix, which can effectively solve the above-mentioned lithium ion diffusion problem, promote more uniform dispersion and deposition of lithium ions, and thus reduce the growth of lithium dendrites.
[0035] In some embodiments, the first polymer is selected from one or more of polyethylene oxide, polyacrylonitrile, polymethyl methacrylate, polyethylene glycol methyl ether acrylate, polyethylene glycol diacrylate, and poly-N-methylpropionamide.
[0036] In some embodiments, the lithium salt is selected from one or more of lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorooxalatoborate, lithium perchlorate, lithium bisoxalatoborate, lithium tetrafluorooxalatophosphate, and lithium difluorobisoxalatophosphate.
[0037] In an embodiment of the present application, the second polymer is selected from one or more of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, vinylidene fluoride-trifluoroethylene, polyacrylonitrile, polymethyl methacrylate, polyethylene glycol diacrylate, and poly N-methylacrylamide.
[0038] In the embodiment of the present application, the second film layer uses the above-mentioned second polymer stable under high voltage, such as poly N-methylpropionamide and polyacrylonitrile. The poly N-methylpropionamide (PMA) molecule contains repeated high dielectric dimethylacetamide (DMAc) units, and polyacrylonitrile (PAN) contains a large number of cyano groups (-CN), which makes PAN have strong polarity. This strong polarity makes PAN easily polarized in an electric field, so that it has a higher dielectric constant, which helps to improve its ability to withstand high voltage.
[0039] In the embodiment of the present application, the ion conductive ceramic is selected from one or more of lithium aluminum titanium phosphate, lithium lanthanum zirconium tantalum oxide, lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide, and lithium phosphorus oxide nitrogen. The above-mentioned ion conductive ceramics belong to oxide solid electrolytes, such as garnet-type lithium lanthanum zirconium oxide (LLZO) with high ionic conductivity, which can reach 10^-3 S / cm at room temperature, which is crucial to improving the charge and discharge efficiency of the battery. In addition, the above-mentioned ion conductive ceramics have a large electrochemical window, which enables them to match high-voltage positive electrode materials and improve the energy density of lithium batteries; and they usually have good thermal stability, and the heat resistance limit is much higher than that of liquid battery separators, which helps to improve the thermal safety of the battery. Compared with liquid electrolytes, solid electrolytes have a higher ignition point and are not easy to ignite, thereby improving the safety of the battery.
[0040] The second aspect of the embodiment of the present application provides a method for preparing the above-mentioned solid electrolyte membrane, comprising the following steps: adding a quaternary ammonium salt to a mixture of a first polymer and a first solvent, stirring to obtain a first mixture, coating the mixture on a glass plate, and drying to form a first film layer; adding a lithium salt to a mixture of a second polymer and a second solvent, then adding powder of an ion conductive ceramic, stirring to obtain a second mixture, coating the mixture on the first film layer to form a second film layer, and drying to obtain a solid electrolyte membrane.
[0041] In the embodiment of the present application, the first solvent is selected from one or more of acetone, anhydrous acetonitrile, N,N-dimethylformamide, and dimethyl sulfoxide. The above-mentioned first solvent is a solvent for dissolving the first polymer. The second solvent is selected from one or more of acetone, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone. The above-mentioned second solvent is a solvent for dissolving the second polymer. Among them, the drying temperature of the first film layer is 20°C to 30°C. The drying temperature of the second film layer is 40°C to 100°C. The coating method of the first mixed liquid and the second mixed liquid can be selected from one or more of the coating method, the spraying method, and the spin coating method.
[0042] In the embodiment of the present application, an ion conductive ceramic, especially an ion conductive ceramic containing lanthanum, is added to the second film layer, and the strong coordination between the first polymer, especially polyacrylonitrile, of the first film layer enhances the bonding force between the ceramic matrix and the polymer. For example, through the strong coordination between La in lithium lanthanum zirconium tantalum oxide (LLZTO) and -CN of polyacrylonitrile (PNA), the PAN coating layer is tightly bonded to the surface of the LLZTO particles, and while constructing a surface strong polarity solid electrolyte membrane with high ionic conductivity, the bonding force between the first film layer and the second film layer is also ensured.
[0043] In some embodiments, in the first mixed solution, the weight percentage of the quaternary ammonium salt is 0.5% to 1.0%, and the weight percentage of the first polymer is 10% to 15%. In other embodiments, in the second mixed solution, the weight percentage of the lithium salt is 2% to 10%, the weight percentage of the second polymer is 10% to 15%, and the weight percentage of the ion conductive ceramic is 5% to 10%.
[0044] A third aspect of the embodiments of the present application provides the use of the above-mentioned solid electrolyte membrane or the solid electrolyte membrane prepared by the above-mentioned preparation method in a solid-state lithium metal battery.
[0045] The solid electrolyte membrane in the embodiments of the present application has greatly improved the high voltage stability, cycle performance and safety performance of the solid-state lithium metal battery.
[0046] In some embodiments, the solid-state lithium metal battery includes a positive electrode plate, a metal lithium negative electrode plate, an electrolyte and a solid electrolyte membrane, wherein the first membrane layer contacts the metal lithium negative electrode plate, and the second membrane layer contacts the positive electrode plate. In the embodiment of the present application, the first membrane layer of the solid electrolyte membrane corresponds to the metal lithium negative electrode side, which can better inhibit the growth of lithium dendrites and improve the safety performance of the lithium metal battery; the second membrane layer corresponds to the positive electrode side, which improves the stability of the lithium metal battery under high voltage. In addition, the double-layer composite structure of the solid electrolyte membrane enhances the mechanical properties of the membrane and improves the safety performance of the lithium metal battery.
[0047] The solid-state lithium metal battery of the embodiment of the present application comprises a positive electrode plate, a metal lithium negative electrode plate, a solid electrolyte membrane and a gel electrolyte. The preparation method of the solid-state lithium metal battery is as follows: Mixing lithium salt, organic solvent, additive and initiator to obtain a gel electrolyte precursor mixed solution; The positive electrode sheet, the metal lithium negative electrode sheet and the solid electrolyte membrane are stacked and / or wound to obtain a bare cell, wherein the first film layer contacts the metal lithium negative electrode side and the second film layer contacts the positive electrode side. The bare cell is packaged to obtain a solid lithium metal cell; A trace amount of gel electrolyte precursor mixed solution is injected into the above-mentioned solid lithium metal battery cell and allowed to stand at 5°C to 10°C for 48 hours; then subjected to high-temperature formation, hot and cold pressing, degassing and vacuum packaging to obtain a solid lithium metal battery.
[0048] In the embodiments of the present application, the positive electrode plates and the solid electrolyte membrane are baked before lamination and / or winding, the baking temperature is 40°C to 120°C, and the processes before formation are all carried out in a drying room with a dew point less than -35°C.
[0049] In the embodiment of the present application, the lithium salt is selected from one or more of lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorooxalatoborate, lithium perchlorate, lithium bis(oxalatoborate), lithium tetrafluorooxalatophosphate, and lithium difluorobis(oxalatophosphate).
[0050] In the embodiments of the present application, the organic solvent is selected from one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, propyl propionate, fluoroethylene carbonate, and methyl trifluoroethyl carbonate.
[0051] In an embodiment of the present application, the additive is a monomer containing an unsaturated bond, and the additive is selected from one or more of polyethylene glycol diacrylate, methyl methacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, ethoxylated trimethylolpropane triacrylate, acrylamide, N,N-methylenebisacrylamide, and sodium alginate.
[0052] In the embodiment of the present application, the initiator is selected from one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, and dibenzoyl peroxide. The above initiator can effectively and specifically initiate the polymerization reaction between the above additives.
[0053] The weight percentage of each component in the precursor mixed solution of the gel electrolyte is: 5% to 15% of lithium salt, 80% to 90% of organic solvent, 2% to 10% of additive, and 0.1% to 0.3% of initiator.
[0054] In the embodiment of the present application, the positive electrode plate includes a positive current collector and a positive active material layer coated on the positive current collector; the positive current collector is aluminum foil, and the positive active material layer includes a positive active material, a first conductive agent and a first binder, wherein the mass ratio of the positive active material, the first conductive agent and the first binder is 80-98:1-10:1-10. The positive active material is selected from one or more of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium manganese oxide, nickel manganese binary material, and lithium nickel cobalt aluminum oxide. The first conductive agent is selected from one or more of conductive graphite, carbon nanotubes, and graphene. The first binder includes polyvinylidene fluoride and / or styrene butadiene rubber.
[0055] All raw materials in the following examples are commercially available.
[0056] Example 1 A solid electrolyte membrane, wherein the first membrane layer comprises the following components: octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate and polyethylene oxide, the mass ratio of the two being 1:10. The second membrane layer comprises the following components: poly N-methyl propionamide, lithium lanthanum zirconium tantalum oxide, and lithium bis(trifluoromethylsulfonyl)imide, the mass ratio of the three being 6:2:3. The thickness of the first membrane layer is 6 μm, and the thickness of the second membrane layer is 10 μm.
[0057] The method for preparing the solid electrolyte membrane comprises the following steps: Octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate was added to the mixture of polyethylene oxide and anhydrous acetonitrile, stirred to obtain a uniform and transparent first mixture, and coated on a glass plate with a scraper, and dried at 20° C. to form a first film layer.
[0058] Lithium bis(trifluoromethylsulfonyl)imide is added to a mixed solution of poly (N-methylpropionamide) and N,N-dimethylacetamide, and stirred to obtain a uniform and transparent solution. Then, lithium lanthanum zirconium tantalum oxide powder is added, and stirred and dispersed evenly to obtain a second mixed solution. The second mixed solution is coated on the first film layer by a slurry spraying method to form a second film layer, and dried at 50°C to obtain a solid electrolyte membrane.
[0059] The solid electrolyte membrane is used for preparing a solid-state lithium metal battery, and the method is as follows: A solid-state lithium metal battery is prepared by matching the positive electrode sheet and the metal lithium negative electrode, so that the above-mentioned solid electrolyte membrane is in the middle of the positive and negative electrodes, and the second membrane layer corresponds to the positive electrode side, and the first membrane layer corresponds to the metal lithium negative electrode side. In a dry environment (dew point does not exceed -35°C), stack them in order to obtain a bare cell. The bare cell is placed in an outer package, and a trace amount of gel electrolyte precursor mixed liquid is injected. After packaging, standing, high-temperature formation, hot and cold pressing, degassing and vacuum packaging, a solid-state lithium metal battery is obtained.
[0060] The positive electrode active material is lithium cobalt oxide, and the mass ratio of the positive electrode active material, conductive graphite, and polyvinylidene fluoride is 96:2:2, and they are baked. The lithium salt is a mixed lithium salt of lithium difluorooxalate borate and lithium hexafluorophosphate, which account for 0.2 wt% and 12 wt% of the precursor of the gel electrolyte precursor mixture, respectively. The organic solvent is fluorinated ethylene carbonate and dimethyl carbonate, which account for 22 wt% and 62 wt% of the precursor of the gel electrolyte precursor mixture, respectively. The additives are polyethylene glycol dimethacrylate and acrylamide, which account for 2.0 wt% and 2.0 wt% of the precursor of the gel electrolyte precursor mixture, respectively. The initiator is azobisisobutyronitrile, which accounts for 0.1 wt% of the precursor of the gel electrolyte precursor mixture.
[0061] Example 2 A solid electrolyte membrane, wherein the first membrane layer comprises the following components: stearamidopropyl hydroxyethyl quaternary ammonium nitrate and polyethylene glycol diacrylate, the mass ratio of the two being 1:9. The second membrane layer comprises the following components: polyvinylidene fluoride-hexafluoropropylene, lithium lanthanum zirconium oxide, and lithium bis(trifluoromethylsulfonyl)imide, the mass ratio of the three being 3:1:1. The thickness of the first membrane layer is 6 μm, and the thickness of the second membrane layer is 10 μm.
[0062] The preparation method of the solid electrolyte membrane is substantially the same as that of Example 1, except that the first solvent is acetone and the second solvent is N,N-dimethylformamide.
[0063] The method for preparing the solid electrolyte membrane for a solid lithium metal battery is the same as that in Example 1 and will not be described again here.
[0064] Example 3 A solid electrolyte membrane, wherein the first membrane layer comprises the following components: stearyl trimethyl quaternary ammonium hydrochloride and polyacrylonitrile, the mass ratio of the two being 1:8. The second membrane layer comprises the following components: polymethyl methacrylate, lithium lanthanum titanium oxide, and lithium bis(fluorosulfonyl)imide, the mass ratio of the three being 5:2:1. The thickness of the first membrane layer is 6 μm, and the thickness of the second membrane layer is 10 μm.
[0065] The preparation method of the solid electrolyte membrane is substantially the same as that of Example 1, except that the first solvent is acetone and the second solvent is N,N-dimethylformamide.
[0066] The method for preparing the solid electrolyte membrane for a solid lithium metal battery is the same as that in Example 1 and will not be described again here.
[0067] Example 4 A solid electrolyte membrane, wherein the first membrane layer comprises the following components: hexadecyl trimethyl ammonium bromide and polyethylene glycol methyl ether acrylate, the mass ratio of the two being 1:11. The second membrane layer comprises the following components: polyacrylonitrile, lithium aluminum titanium phosphate, and lithium perchlorate, the mass ratio of the three being 5:2:2. The thickness of the first membrane layer is 6 μm, and the thickness of the second membrane layer is 10 μm.
[0068] The preparation method of the solid electrolyte membrane is substantially the same as that of Example 1, except that the first solvent is N,N-dimethylacetamide and the second solvent is acetone.
[0069] The method for preparing the solid electrolyte membrane for a solid lithium metal battery is the same as that in Example 1 and will not be described again here.
[0070] Example 5 A solid electrolyte membrane, wherein the first membrane layer comprises the following components: octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate and poly N-methyl propionamide, the mass ratio of the two being 1:12. The second membrane layer comprises the following components: polyethylene glycol diacrylate, lithium titanium aluminum phosphate, and lithium difluorobisoxalate phosphate, the mass ratio of the three being 5:3:2. The thickness of the first membrane layer is 6 μm, and the thickness of the second membrane layer is 10 μm.
[0071] The preparation method of the solid electrolyte membrane is substantially the same as that of Example 1, except that the first solvent is acetone and the second solvent is N,N-dimethylformamide.
[0072] The method for preparing the solid electrolyte membrane for a solid lithium metal battery is the same as that in Example 1 and will not be described again here.
[0073] Comparative Example 1 This comparative example is substantially the same as Example 1, except that the first film layer does not include a quaternary ammonium salt.
[0074] Comparative Example 2 Conventional polyethylene oxide (PEO)-lithium lanthanum zirconium tantalum oxide (LLZTO) is used as a solid electrolyte membrane, and the solid electrolyte membrane is a single layer. The thickness is 15 μm. The same positive electrode, metal lithium negative electrode and trace gel electrolyte precursor mixed solution as in Example 1 are used, and the same process as in Example 1 is used to complete the preparation of the solid lithium metal battery of Comparative Example 2.
[0075] The solid-state lithium metal batteries prepared in Examples 1 to 5 and Comparative Examples 1 and 2 were subjected to cycle test experiments and safety monitoring. The cycle test results are shown in Tables 1 and Figure 1 ,The safety test results are shown in Table 2.
[0076] Table 1 Performance test results of solid-state lithium metal battery (capacity 1Ah)
[0077] Table 2 Safety test results of solid-state lithium metal batteries (capacity 1Ah)
[0078] According to Table 1, Table 2 and Figure 1 It can be seen from the data that compared with the solid-state lithium metal batteries of Comparative Examples 1 and 2, the solid-state lithium metal batteries of each embodiment have better first cycle efficiency, capacity utilization, cycle stability and safety performance, and are not prone to short circuit, reflecting the better electrochemical stability of the double-layer solid electrolyte membrane and widening the electrochemical window. Figure 1 The LSV test is performed after the solid electrolyte membrane of the comparative example and the embodiment is assembled with a button. The horizontal axis is voltage and the vertical axis is current density. It is usually judged that when the current changes greatly, it proves that the interface of the electrolyte membrane has undergone serious oxidation at this voltage, which is the oxidation potential of the electrolyte membrane. Figure 1 It can be seen that the oxidation potential of the solid electrolyte membranes of Comparative Examples 1 and 2 is about 4.7 V, while the oxidation potential of the embodiments is basically above 5 V. By comparison, it can be concluded that the embodiments have better high voltage resistance characteristics.
[0079] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A solid electrolyte membrane, characterized in that: The invention comprises a first membrane layer and a second membrane layer, wherein the first membrane layer comprises the following components: a quaternary ammonium salt and a first polymer; and the second membrane layer comprises the following components: a lithium salt, a second polymer and ion conductive ceramics.
2. The solid electrolyte membrane according to claim 1, characterized in that In the first film layer, the mass ratio of the quaternary ammonium salt to the first polymer is 1:8-12; and / or, in the second film layer, the mass ratio of the lithium salt, the second polymer and the ion conductive ceramic is 6:1-3:1-3.
3. The solid electrolyte membrane according to claim 1, characterized in that The thickness of the first film layer is 5-10 μm, and the thickness of the second film layer is 5-10 μm.
4. The solid electrolyte membrane according to any one of claims 1 to 3, characterized in that: The quaternary ammonium salt is selected from one or more of octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate, hexadecyl trimethyl ammonium bromide, stearamidopropyl hydroxyethyl quaternary ammonium nitrate, and stearyl trimethyl quaternary ammonium hydrochloride; The first polymer is selected from one or more of polyethylene oxide, polyacrylonitrile, polymethyl methacrylate, polyethylene glycol methyl ether acrylate, polyethylene glycol diacrylate, and poly-N-methylpropionamide.
5. The solid electrolyte membrane according to any one of claims 1 to 3, characterized in that: The lithium salt is selected from one or more of lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorooxalatoborate, lithium perchlorate, lithium bisoxalatoborate, lithium tetrafluorooxalatophosphate, and lithium difluorobisoxalatophosphate; The second polymer is selected from one or more of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, vinylidene fluoride-trifluoroethylene, polyacrylonitrile, polymethyl methacrylate, polyethylene glycol diacrylate, and poly-N-methylpropionamide; The ion conductive ceramic is selected from one or more of lithium aluminum titanium phosphate, lithium lanthanum zirconium tantalum oxide, lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide, and lithium phosphorus oxide nitrogen.
6. The method for preparing a solid electrolyte membrane according to any one of claims 1 to 5, characterized in that: The following steps are involved: Adding the quaternary ammonium salt to a mixture of the first polymer and the first solvent, stirring to obtain a first mixture, coating the mixture on a glass plate, and drying to form the first film layer; The lithium salt is added to a mixture of the second polymer and the second solvent, and then the powder of the ion conductive ceramic is added and stirred to obtain a second mixture, which is then coated on the first film layer to form the second film layer, and dried to obtain the solid electrolyte membrane.
7. The method for preparing a solid electrolyte membrane according to claim 6, characterized in that: The first solvent is selected from one or more of acetone, anhydrous acetonitrile, N,N-dimethylformamide, and dimethyl sulfoxide; the second solvent is selected from one or more of acetone, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.
8. The method for preparing a solid electrolyte membrane according to claim 6, characterized in that: In the first mixed solution, the weight percentage of the quaternary ammonium salt is 0.5% to 1.0%, and the weight percentage of the first polymer is 10% to 15%; and / or, In the second mixed solution, the weight percentage of the lithium salt is 2% to 10%, the weight percentage of the second polymer is 10% to 15%, and the weight percentage of the ion conductive ceramic is 5% to 10%.
9. Use of the solid electrolyte membrane according to any one of claims 1 to 5 or the solid electrolyte membrane prepared by the preparation method according to any one of claims 6 to 8 in a solid-state lithium metal battery.
10. The use according to claim 9, characterized in that: The solid-state lithium metal battery comprises a positive electrode plate, a metal lithium negative electrode plate, an electrolyte and the solid electrolyte membrane, the first membrane layer is in contact with the metal lithium negative electrode plate, and the second membrane layer is in contact with the positive electrode plate.